Pengaruh Kualitas Sumber Daya Manusia, Penggunaan Media Sosial Dan Modal Usaha Terhadap Kinerja Karyawan Pada CV Karisa Pratama Di Pangandaran - Yosha Rosha Rosmayantie (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This research is motivated by the problem of employee performance that is still not optimal. The prnyrbabya factors are the quality of human resources, the use of social media and business capital. Thus, the purpose of this study was to determine the effect of the quality of human resources, the use of social media and business capital on the performance of employees at CV Karisa Pratama in Pangandaran. The method used is a quantitative descriptive method, with the following research results. The quality of human resources has a positive and significant effect on employee performance. This means that if the quality of human resources increases, it will be followed by an increase in employee performance. The use of social media has a positive and significant effect on employee performance. This means that if the use of social media increases, it will be followed by an increase in employee performance. Business capital has a positive and significant effect on employee performance. This means that if the business capital increases, it will be followed by an increase in employee performance. The quality of human resources, the use of social media and business capital have a positive and significant effect on employee performance. This means that if the quality of human resources, the use of social media and business capital, increases, it will be followed by an increase in employee performance